To Test or Not to Test? The Graduate Record Examinations: Predictive Validity toward Graduate Study Success on Research Masters' Programs in a Large European University - Anastasia Kurysheva; Gönül Dilaver; Christine Merie Fox; Harrison Kell; Matthias Robert Kern; Harold V. M. van Rijen (MDPI AG, 2024)
Graduate admissions committees in Europe have a challenging task of selecting students from an increasingly large pool of candidates with diverse application files. Graduate standardized testing can ease the comparison of application files. The purpose of this study was to examine whether the Graduate Record Examinations (GRE) is predictive of several dimensions of graduate success on English-taught research masters' programs in science, technology, engineering, and mathematics at a large European university. The data from 167 masters' students were collected. Hierarchical regression analyses were conducted. All GRE scales predicted Graduate Grade Point Average. Individual GRE scales predicted internship grade and supervisors' assessments of students' research performance and the content of their research report. None of the individual GRE scales predicted supervisors' assessments of students' practical skills, but the three GRE scales taken together improved the explanatory power of the model. The structure and style of students' research reports was not predicted by the GRE. All relationships were held after accounting for socioeconomic status. Overall, the GRE appeared as a reasonable predictor of graduate study success. Both the benefits and drawbacks of the implementation of the GRE in European masters' programs are discussed, as well as the legal limitations.